The Influence of Ice Breaking on Students' Interest in Islamic Religious Education Learning at SMP Negeri 3 Cukuhbalak Tanggamus - Mutmainnah; Meriyati; Chairul Amriyah (CV. Creative Tugu Pena, 2024)
This research was motivated by students' lack of interest in learning PAI. Teachers still rarely apply ice breaking in their learning process. This research aims to find out whether there is an influence of ice breaking on students' interest in learning in PAI subjects at SMP N 3 Cukuhbalak Tanggamus. This research was conducted at SMP N 3 Cukuhbalak Tanggamus Regency. This research is quantitative research using experimental methods and Quasi-experiment design. The research population was all students at SMP N 3 Cukuhbalak Tanggamus. The sample for this research was Class VII students, consisting of Class VII A for the Experiment group and Class VIIB, for the Control group. The data collection technique in this research is a questionnaire as the main instrument, while the data analysis technique uses the Wilcoxon test and the Mann Whitney test. The research results showed that: Based on the data from the Wilcoxon Test, the Asym Sig (2-Tailed) data was 0.000 < 0.05 or Ha was accepted. So it can be concluded that there is an influence of ice breaking on students' interest in learning in PAI subjects at SMP N 3 Cukuhbalak Tanggamus. Meanwhile, the results of the Mann Whitney test obtained a significance value of 0.000 < 0.05, so there was a significant difference in the learning interest scores of class VII students at SMPN 3 Cukuhbalak between the group that implemented ice breaking and the group that did not apply ice breaking.